2020
DOI: 10.1101/2020.06.11.146753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into glycan import by a prominent gut symbiont

Abstract: 24In Bacteroidetes, one of the dominant phyla of the mammalian gut, active uptake of large 25 nutrients across the outer membrane is mediated by SusCD protein complexes via a "pedal 26 bin" transport mechanism. However, many features of SusCD function in glycan uptake remain 27 unclear, including ligand binding, the role of the SusD lid and the size limit for substrate 28 transport. Here we characterise the β2,6 fructo-oligosaccharide (FOS) importing SusCD from 29Bacteroides thetaiotaomicron (Bt1762-Bt1763) to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Indeed, the TBDTs identified by our search demonstrate that most B. theta TBDTs that are devoted to glycan uptake are 200–300 amino acids longer than the well‐studied TBDTs involved in iron uptake in Gram‐negative pathogens. The recent crystal structures of three TBDTs from Bacteroidetes demonstrate that some of this additional sequence is devoted toward elongated loops at the extracellular face of the barrel (Figure 1c) (Glenwright et al., 2017; Gray et al., 2021; Madej et al., 2020). These loops in part engage with the ligand‐binding SusD protein that caps the barrel, as described later.…”
Section: Structural Domains Within B Thetaiotaomicron Tbdtsmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, the TBDTs identified by our search demonstrate that most B. theta TBDTs that are devoted to glycan uptake are 200–300 amino acids longer than the well‐studied TBDTs involved in iron uptake in Gram‐negative pathogens. The recent crystal structures of three TBDTs from Bacteroidetes demonstrate that some of this additional sequence is devoted toward elongated loops at the extracellular face of the barrel (Figure 1c) (Glenwright et al., 2017; Gray et al., 2021; Madej et al., 2020). These loops in part engage with the ligand‐binding SusD protein that caps the barrel, as described later.…”
Section: Structural Domains Within B Thetaiotaomicron Tbdtsmentioning
confidence: 98%
“…Additionally, surveys of TBDTs across bacteria have often noted the key differences between characterized TBDT largely from Enterobacteria and predicted TBDTs in the Bacteroidetes (Blanvillain et al., 2007; Koebnik, 2005). Today, biochemical studies of Bacteroides PUL and the associated TBDTs have begun to give us a better picture of how the TBDTs encoded by the Bacteroidetes share similar structure and function to the classical TBDT while also allowing for novel structures and functions (Glenwright et al., 2017; Gray et al., 2021; Madej et al., 2020). Here, we use Pfam domain analysis of the 121 predicted TBDTs in Bacteroides thetaiotaomicron to review what is currently known and what work remains to be done to better understand sugar transport and the broader role of TBDTs in the Bacteroidetes.…”
Section: Tonb‐dependent Transporters In the Bacteroidetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Landmark structural studies revealed that the TBDT–SGBP complexes encoded by pairs of susC / susD gene homologues (viz., SusC H and SusD H proteins) enable polysaccharide breakdown products produced at the cell surface to transit the outer membrane. This protein pair operates through a ‘pedal‐bin’ mechanism, involving the coordinated opening and closing of the lid formed by the SusD H SGBP with movement of the plug domain of the SusC H TBDT (Gray et al ., 2020). Proper assembly of this complex is thus essential to glycan utilization, such that deletion of the SusD H SGBP from a gnPUL abolishes growth on the cognate glycan (Anderson and Salyers, 1989a; 1989b; Tancula et al ., 1992; Reeves et al ., 1996; 1997; Cho and Salyers, 2001; Koropatkin et al ., 2008; 2009; Cameron et al ., 2012; Karunatilaka et al ., 2014; Tauzin et al ., 2016; Tamura et al ., 2019).…”
Section: Gram‐negative Polysaccharide Utilization Locimentioning
confidence: 99%